Motion of Human Nature towards "Imago Dei" in the Thought of St. Maximus the Confessor - Hupalo, Mariia (Vox Patrum, 2020)
St. Maximus the Confessor has a profound understanding of human mutability and human striving for the divine. In his opinion, this striving reflects the very meaning of human existence, which is to be in relation and ultimately in communion with God. Human nature cannot exist without this mutability; at the same time Maximus regards it as positive and intended by God, contrary to Origen’s understanding of the motion of souls. The idea of mutability and relationality of human nature has a profound impact on modern philosophy, but still needs clarification. Maximus might represent an anthropology that is appealing to our time and at the same time deeply grounded in Christian tradition. This article is an attempt to sketch the main lines of Maximus’ argumentation.